Diversity of Managerial Perspectives from Inside China - Foo, Check Teck.; SpringerLink (Online service) (Singapore : Springer Singapore(Imprint), 2016)
This book includes research presented at the Global Chinese Management Studies Conferences held in Singapore between 2011 and 2014. It covers managerial themes from China that are associated with eco-labels, institutional changes in the context of governance, fusion accounting information, consumers on insuring, corporate social responsibility, financial warning systems, new product development, entrepreneurship, polycentric patterns and even destructive leadership. The papers were written by leading academics from Mainland China, Taiwan, Hong Kong, and Singapore whose perspectives represent a departure from conventional managerial practices. Diversity of Managerial Perspectives from Inside China is essential reading for all researchers interested in the development and significance of management-related topics in the Chinese market.
Part I: Introduction -- Chapter 1: Overview: Governance, Risk, Technology and Value -- Part II: Governance -- Chapter 2: Managing Corporate Social Responsibility (CSR) in China -- Chapter 3: Transformation and Institutional Change of Corporate Governance -- Chapter 4: Emerging Polycentric Pattern in Governing Transitional China -- Chapter 5: Accounting Information Fusion for Decision Making -- Part III: Risk -- Chapter 6: Early Warning System for Finance -- Chapter 7: New Consumers' Perspective in Insuring Earthquakes -- Chapter 8: Corporate Eleemosynary Behavior -- Part IV: Technology -- Chapter 9: Technology Management for New Product Development -- Chapter 10: Entrepreneurial Innovation and Performance in Forestry -- Chapter 11: Eco-Labeling, Visioning and Integration -- Part V: Values -- Chapter 12: Chinese Philosophy, Values and Culture -- Chapter 13: Yin-Yang Harmony for Management -- Chapter 14: Destructive Leadership, Employees' Voice and Organization.
Keywords: Entrepreneurship; Organization; Finance, general; Innovation/Technology Management